A quasi-experimental study to assess the effectiveness of behavior therapy on childhood adjustment issues (social anxiety disorder) among the children studying between 5th to 7th standard at selected schools of Surat, Gujarat - Biradar, Sateesh; Patil, Ashwini (Journal of Neonatal Surgery, 2025)
Introduction: Children are the nation's future and its cornerstone. However, they are more likely to experience childhood adjustment problems now. One such problem is social anxiety disorder, a condition marked by social avoidance and apprehension that impairs social functioning. Aim of the study: This study aimed to assess the effectiveness of behaviour therapy among children studying between 5th-7th standard and reduce their social anxiety levels. Material and Method: A quasi-experimental (non-randomized control group study design) was used to assess the effectiveness of the behaviour therapy among children having social anxiety disorder studying between 5th-7th standard at selected schools of Surat. Structured social anxiety questionnaires (SAQ-C20) were used to collect the demographic data and assess the level of social anxiety. Both descriptive and inferential statistics were applied to the data analysis. Results: Severe social anxiety was present in most of the samples chosen for the experimental group. For fifteen days, behavior therapy was delivered by the investigators to lower the degree of social anxiety. Following the period of treatment, a post-test was given, and statistical analysis of the data gathered reveals that the experimental group's social anxiety score decreased both before and after behavior therapy was administered from 54.266±5.988 to 37.866 ± 9.354, (p <0.001); a decrease of 16.4 ± 5.89, whereas it was very small in the control group from 43.766±1.695 to 42.366± 1.809, (p <0.05); a decrease of 1.4 ± 0.56, mean social anxiety disorder score was higher in the experimental group (54.26±5.988) compared to the control group (43.76±1.69). Paired t-test results showed that the social anxiety disorder score was higher in the pre-test score (54.26 ±5.988) compared to the post-test score (37.86±9.354), t=15.227 among the experimental group whereas almost the same in the pre-test score (43.76 ±1.695) compared to post-test score (42.36±1.809), t=13.614 among the control group, p<0.05. Conclusion: Based on the results, it was determined that there is a statistically significant difference between the control and experimental groups' pre- and post-treatment levels of social anxiety.